ECOLOGICAL BALANCE OF SETHUSAMUDRAM CANAL, INDIA: special reference to mangrove ecosystem - Oswin D Stanley (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Impact of Sethusamudram canal on the southeast coastal ecosystems is assumed to be diverse. The paper discusses the significance and status of the mangrove ecosystem in specific to Tamil Nadu coast, the impact of the project on the mangroves, the presumptive ecological and economical dynamics this also suggests a rational ecosystem management tool.